Efektivitas Mediator dalam Hubungan Industrial: Rekonstruksi Peran Preventif dalam Mencegah Eskalasi Perselisihan Buruh - Allaysha Adindaputri Kirani; Gunardi Lie (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the effectiveness of mediators in preventing the escalation of labor disputes within the framework of Indonesian industrial relations law. Employing a normative legal research method with statutory and conceptual approaches, the analysis focuses on the regulatory structure governing mediation, particularly Law Number 2 of 2004, Law Number 13 of 2003 as amended by Law Number 11 of 2020, and their implementing regulations. The findings reveal that mediation is formally recognized as a dispute resolution mechanism, yet its function remains predominantly reactive and oriented toward post-conflict settlement. From a conceptual perspective, legal effectiveness should also encompass the capacity of norms to prevent disputes from escalating through early intervention and structured dialogue. The study identifies normative gaps in the regulation of mediators, particularly regarding preventive roles, institutional integration, and competency development. The research argues for a normative reconstruction that strengthens the strategic role of mediators, incorporates restorative approaches, and supports digital mediation mechanisms. Such transformation is essential to ensure sustainable conflict prevention and to promote balanced industrial relations between workers and employers.